Achieving operational synergy between different adaptive façade technologies - H. Alkhatib; N. O’Neill; B. Norton; P. Lemarchand; D.T.J. O’Sullivan (Results in Engineering)
Adaptive building facades provide variable shading, thermal insulation, and ventilation. These can be combined in a specific configuration for specific ambient and internal condition to minimise energy used to meet the comfort and well-being of building occupants. Careful design and operation are necessary to ensure that system attributes work together effectively. Control frameworks for adaptive façade systems that optimally vary the contribution of distinct attributes as condition change have not been fully developed. This paper (i) presents the development and fabrication of a multi-functional façade, (ii) explores possible means and challenges of achieving optimal control of an adaptive façade with multiple functionalities and (iii) investigates energy consumption and occupancy comfort through both experiment and simulation. The results showed that the adaptive façade system resulted in 39.5 % heating energy savings, 18.7 % cooling energy savings, and 4.3 % lighting energy savings compared to a conventional façade without adaptive technologies. Daylight comfort was improved by 7.3 %, highlighting the effectiveness of integrating multiple façade functionalities under a unified control framework.